Entrainment and detrainment in cumulus convection: an overview. (7th June 2012) - de Rooy, Wim C.; Bechtold, Peter; Fröhlich, Kristina; Hohenegger, Cathy; Jonker, Harm; Mironov, Dmitrii; Pier Siebesma, A.; Teixeira, Joao; Yano, Jun‐Ichi
Abstract Entrainment and detrainment processes have been recognised for a long time as key processes for cumulus convection and have recently witnessed a regrowth of interest mainly due to the capability of large‐eddy simulations (LES) to diagnose these processes in more detail. This article has a twofold purpose. Firstly, it provides a historical overview of the past research on these mixing processes, and secondly, it highlights more recent important developments. These include both fundamental process studies using LES aiming to improve our understanding of the mixing process, but also more practical studies targeted toward an improved parametrised representation of entrainment and detrainment in large‐scale models. A highlight of the fundamental studies resolves a long‐lasting controversy by showing that lateral entrainment is the dominant mixing mechanism in comparison with the cloud‐top entrainment in shallow cumulus convection. The more practical studies provide a wide variety of new parametrisations with sometimes conflicting approaches to the way in which the effect of the free tropospheric humidity on the lateral mixing is taken into account. An important new insight that will be highlighted is that, despite the focus in the literature on entrainment, it appears that it is rather the detrainment process that determines the vertical structure of the convection in general and the mass flux especially. Finally, in order to speed up progress and stimulate convergence in future parametrisations, stronger and more systematic use of LES is advocated. Copyright © 2012 Royal Meteorological Society